FLUORIDE CONCENTRATIONS IN TABLE SALTS SOLD IN SUPERMARKETS OF BOGOTA, COLOMBIA - Carolina Baez-Quintero, Liliana [UNESP]; Botazzo Delbem, Alberto Carlos [UNESP]; Harold Estrada-Montoya, John; Emi Nagata, Mariana [UNESP]; Pelim Pessan, Juliano [UNESP] (Int Soc Fluoride Research, 2021)
Purpose: To determine the fluoride (F) concentrations in table salts sold in Bogota, Colombia, as well as to verify whether the values were consistent with the information provided by the manufacturers and with the standards of the national program of domestic salt fluoridation. Materials and methods: Twenty-eight different samples of table salt were purchased in the main supermarkets of Bogota, comprising coarse, refined, and seasoned salts. Fluoride content was analyzed with an ion-specific fluoride electrode. Results: Mean (SD) F concentration for all samples was 133.8 (51.0) ppm F, ranging from 4.8 to 225.7 ppm F. The majority of samples (71%) had values below those recommended by the national program of salt fluoridation in Colombia. Conclusion: Most of the salts analyzed did not comply with the legislation for salt fluoridation in Colombia. Therefore, monitoring of the fluoride concentrations in salts for human consumption should be performed on a regular basis, so that fluoride levels are kept at safe and effective levels for caries control, without increasing the risk of dental fluorosis.
Keywords: Diet; Fluorides; Public health surveillance; Salt fluoridation; Sodium chloride